Cell Biology
Cell Biology is a textbook for students of biotechnology and allied disciplines to understand the functioning of a cellâ€"the fundamental unit of life. The book offers a comprehensive and detailed coverage of various themes of the subject, including the fundamental concepts of membrane transport, cells of the immune system, haematopoiesis, genetic mechanism in cells, metabolic pathways, germ cells, cytoskeleton, and cell signalling. The later chapters focus on cell differentiation, stem cell biology, and various analytical techniques employed in cell biology. Each chapter is reinforced with learning features such as summary of concepts, terms to remember, review questions, and multiple-choice questions that help in effective recapitulation.